Volvo Group and Sustainable Sourcing - A Benchmark of Global Organizations - Ihrelius, Johanna; Wångdahl, Sara (My University, 2013)
The strategic importance of purchasing is increasing, and as a result an additional aspect of purchasing; that of contributing to a decreased impact on the natural environment is being discussed. As environmental factors are becoming increasingly important for internal and external stakeholders, such as customers and investors, companies are motivated to change, in order to remain competitive, to provide what the customer request and to fulfill laws and regulation. Making environmentally friendly choices is often considered as costly. However, efficient environmental work can be argued to increase customer value and increase profitability by reducing waste and energy consumption. The purpose of this thesis was to identify factors that are beneficiary both economically and environmentally when sourcing, by conducting a benchmark with Volvo and prominent companies working successfully with sustainability. This problem was studied by dividing the question into three research questions that was fulfilled by a literature study as well as with a benchmark with selected companies. The participating companies act on completely different markets but were selected due to their comparable processes such as working and sourcing globally. The analysis identified several factors where the efforts to reduce environmental impact were associated with increased profitability. The participating companies work in radically different ways regarding some factors while there was an agreement considering other factors. All the participating companies incorporate sustainability in their company and while it is clearly stated in the companies’ core values that the companies work to reduce their environmental impact it is only when the efforts are associated with cost reductions that they are being performed. This supports the belief that to lessen the environmental impact it is critical to also find economical incitement to do so. The factors associated with profitability and decreased environmental impact are creation of joint ventures and co-development with key suppliers, demands of clean engines, as well as engine and fuel development, to use sustainable sourcing in the marketing, to calculate the landed cost and to work with waste reduction. The factors that Volvo Group are recommended to implement are; co-operation with suppliers to develop more sustainable transportation, conduct their own audits and increase frequency of those audits and a higher degree of compliance with the code of conduct. In addition to these factors is it also suggested that Volvo Group calculate landed cost in all procurements.
Keywords: Övrig industriell teknik och ekonomi; Produktion; Transport; Other industrial engineering and economics; Production; Transport